2015
DOI: 10.1016/j.yqres.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Lake core record of Grinnell Glacier dynamics during the latest Pleistocene deglaciation and the Younger Dryas, Glacier National Park, Montana, USA

Abstract: Few records in the alpine landscape of western North America document the geomorphic and glaciologic response to climate change during the Pleistocene–Holocene transition. While moraines can provide snapshots of glacier extent, high-resolution records of environmental response to the end of the Last Glacial Maximum, Younger Dryas cooling, and subsequent warming into the stable Holocene are rare. We describe the transition from the late Pleistocene to the Holocene using a ~ 17,000-yr sediment record from Swiftc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…To query the literature on western U.S. sediment yields, we examined published studies of fluvial sediment flux and lake sedimentation (Figure 4 and Tables 1 and S1). S1); 10, Grass Valley Creek near Lewiston, CA (Table S1); 11, Ward Creek near Tahoe, CA (Table S1); 12, Dry Creek near Geyserville, CA (Table S1); 13, Badger Creek near Howard, CO (Table S1); 14, Monument Creek at Colorado Springs, CO (Table S1); 15, Powder River at Moorhead, MT (Table S1); 16, Clark Fork at Deer Lodge, MT (Table S1); 17, Clark Fork near Bonner, MT (Table S1); 18, Animas River at Farmington, NM (Table S1); 19, Rio Puerco near Guadalupe, NM (Table S1); 20, Rio Chama near Chamita, NM (Table S1); 21, Palouse River at Hooper, WA (Table S1); 22, Rock Creek at Atlantic City, WY (Table S1); 23, Fivemile Creek near Pavillion, WY (Table S1); 24, Fifteen Mile Creek near Worland, WY (Table S1); 25, Badwater Creek at Bonneville, WY (Table S1); 26, Powder River at Arvada, WY (Table S1); 27, San Lorenzo River (East, Stevens, et al, 2018); 28, Skagit River (Curran et al, 2016); 29, Walker Lake (Hatchett et al, 2015); 30, Jenny Lake (Larsen et al, 2016); 31, Swiftcurrent Lake (Schachtman et al, 2015); 32, four lakes studied by Bracht-Flyr and Fritz (2012); 33, two lakes studied by Schuman and Serravezza (2017); 34, lakes in the San Juan Mountains (Arcusa et al, 2019;Neff et al, 2008;Routson et al, 2019); 35, seven lakes studied by Munroe et al, (2015); 36, Stoneman Lake (Hasbargen, 1994); 37, Bison Lake (Anderson et al, 2015); 38, Englebright Lake (Snyder et al, 2004;…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To query the literature on western U.S. sediment yields, we examined published studies of fluvial sediment flux and lake sedimentation (Figure 4 and Tables 1 and S1). S1); 10, Grass Valley Creek near Lewiston, CA (Table S1); 11, Ward Creek near Tahoe, CA (Table S1); 12, Dry Creek near Geyserville, CA (Table S1); 13, Badger Creek near Howard, CO (Table S1); 14, Monument Creek at Colorado Springs, CO (Table S1); 15, Powder River at Moorhead, MT (Table S1); 16, Clark Fork at Deer Lodge, MT (Table S1); 17, Clark Fork near Bonner, MT (Table S1); 18, Animas River at Farmington, NM (Table S1); 19, Rio Puerco near Guadalupe, NM (Table S1); 20, Rio Chama near Chamita, NM (Table S1); 21, Palouse River at Hooper, WA (Table S1); 22, Rock Creek at Atlantic City, WY (Table S1); 23, Fivemile Creek near Pavillion, WY (Table S1); 24, Fifteen Mile Creek near Worland, WY (Table S1); 25, Badwater Creek at Bonneville, WY (Table S1); 26, Powder River at Arvada, WY (Table S1); 27, San Lorenzo River (East, Stevens, et al, 2018); 28, Skagit River (Curran et al, 2016); 29, Walker Lake (Hatchett et al, 2015); 30, Jenny Lake (Larsen et al, 2016); 31, Swiftcurrent Lake (Schachtman et al, 2015); 32, four lakes studied by Bracht-Flyr and Fritz (2012); 33, two lakes studied by Schuman and Serravezza (2017); 34, lakes in the San Juan Mountains (Arcusa et al, 2019;Neff et al, 2008;Routson et al, 2019); 35, seven lakes studied by Munroe et al, (2015); 36, Stoneman Lake (Hasbargen, 1994); 37, Bison Lake (Anderson et al, 2015); 38, Englebright Lake (Snyder et al, 2004;…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
“…Locations of studies used to assess whether hydroclimatically driven increases in watershed sediment yields are apparent (Question 2; section 3.2); one of 44 studies answered Question 2 affirmatively. Numbers refer to study locations as follows: 1, study of four watersheds by Warrick et al (2015); 2, study of 10 watersheds by Bywater-Reyes et al (2018); 3, Redwood Creek(Madej & Ozaki, 1996); 4, study of eight watersheds byWarrick et al (2013); 5, study of 21 watersheds byGray (2018), shown as several groups; 6, Santa Clara River(Barnard & Warrick, 2010;Gray, 2018); 7, Walnut Gulch Experimental Watershed(Gao et al, 2013;Goodrich et al, 2008;Nearing et al, 2007Nearing et al, , 2015; 8, six sites evaluated byPolyakov et al (2016); 9, Paria River at Lees Ferry, AZ (TableS1); 10, Grass Valley Creek near Lewiston, CA (TableS1); 11, Ward Creek near Tahoe, CA (TableS1); 12, Dry Creek near Geyserville, CA (TableS1); 13, Badger Creek near Howard, CO (TableS1); 14, Monument Creek at Colorado Springs, CO (TableS1); 15, Powder River at Moorhead, MT (TableS1); 16, Clark Fork at Deer Lodge, MT (TableS1); 17, Clark Fork near Bonner, MT (TableS1); 18, Animas River at Farmington, NM (TableS1); 19, Rio Puerco near Guadalupe, NM (TableS1); 20, Rio Chama near Chamita, NM (TableS1); 21, Palouse River at Hooper, WA (TableS1); 22, Rock Creek at Atlantic City, WY (TableS1); 23, Fivemile Creek near Pavillion, WY (TableS1); 24, Fifteen Mile Creek near Worland, WY (TableS1); 25, Badwater Creek at Bonneville, WY (TableS1); 26, Powder River at Arvada, WY (TableS1); 27, San Lorenzo River(East, Stevens, et al, 2018); 28, Skagit River(Curran et al, 2016); 29, Walker Lake(Hatchett et al, 2015); 30, Jenny Lake(Larsen et al, 2016); 31, Swiftcurrent Lake(Schachtman et al, 2015); 32, four lakes studied by Bracht-Flyr and Fritz (2012); 33, two lakes studied by Schuman and Serravezza (2017); 34, lakes in the San Juan Mountains(Arcusa et al, 2019;Neff et al, 2008;Routson et al, 2019); 35, seven lakes studied byMunroe et al, (2015); 36, Stoneman Lake(Hasbargen, 1994); 37, Bison Lake(Anderson et al, 2015); 38, Englebright Lake(Snyder et al, 2004;Snyder et al, 2006); 39, Lake Quinault(Smith et al, 2019); 40, Alder Lake, Nisqually basin...…”
mentioning
confidence: 99%
“…From proximal to distal from the inlet (sites 1-3, respectively), those rates were 0.19, 0.41, and 0.52 mm/yr. The average sedimentation rate for the Schachtman et al (2015) core, farther from the inlet (Fig. 16), is 0.59 mm/year.…”
Section: Discussionmentioning
confidence: 99%
“…From proximal to distal from the inlet (sites 1-3, respectively), those rates were 0.19, 0.41, and 0.52 mm/yr. The average sedimentation rate for the Schachtman et al (2015) core, farther from the inlet, is 0.59 mm/year. Sedimentation rates increase with distance from the inlet, which was surprising: we originally hypothesized that more transported inlet stream is eroding as well as depositing sediment, and that some transported sediment may bypass the delta entirely, especially during high water discharge periods.…”
Section: Grinnell Valleymentioning
confidence: 99%
“…In 2005, 2010, and 2014, we collected lake cores in Swiftcurrent Lake, Lake Josephine, and lower Grinnell Lake, all of which are located downstream of Grinnell Glacier (Figures 1 & 2). Work done on these cores by previous students (many of them as part of Keck projects) has provided additional constraints on climate and environmental history in the basin since the end of the Last Glacial Maximum (e.g., MacGregor et al, 2011;Schachtman et al, 2015). The overarching goal of the project this year was to understand sediment transport and deposition in the lower end of Swiftcurrent and Grinnell valleys, and how those processes document changes in environment and climate over centuries to millennia.…”
Section: Introductionmentioning
confidence: 99%